Specters of ecocriticism - Jarosław Woźniak (Przestrzenie Teorii)
For years ecocriticism has been almost completely absent in Polish humanities, and although it has become known to a wider group of academics and literary critics and has gained some recognition, it is still not widely acknowledged. This situation raises two basic questions: first, what are the reasons for the low level of interest in ecocriticism in Polish humanities?; secondly, what are the chances and conditions for establishing ecocriticism in the Polish academia? The author assumes that there are spectral remains of the early stages of ecocriticism that still haunt it, casting a shadow on current research and hindering the reception of ecocriticism in Poland. The main specters that haunt ecocriticism are: the specter of romanticism, an anti-theoretical attitude, and naive realism that sprout from the first wave of ecocriticism. Referring to the latest currents in ecological criticism, the author indicates further directions in which Polish ecocriticism should develop in order to be freed from the persecuting specters of the past.